Spectrophotometric Analysis Assay for the Measurement of Arsenic Using Nanocomposite of Silica and Graphene. Issue 1 (February 2020) - Uda, M. N. A.; Hashim, Uda; Subash Gopinath, C. B.; Afnan Uda, M. N.; Parmin, N. A.; Adam, Hussain; Ibrahim, Nur Hulwani
Abstract: According to media reports in today's world, millions of people across the globe are suffering from arsenic (As) toxicity. Arsenic heavy metal occurs in different oxidative states in the environment and enters in the food chain through soil and water. In the agricultural field, irrigation with arsenic contaminated water has a higher level of arsenic contamination on the top soil, which may eventually affects the quality of crop production. The major crop like rice requires a considerable amount of water to complete its lifecycle. In Asian countries like Malaysia, Brunei, Indonesia, and Thailand, arsenic intake from rice diet is significantly higher, as rice plants have a special ability to take up arsenic from the soil and water used in irrigation. The transfer of arsenic from soil to plant systems is a serious issue that leads to considerable human exposure in a dangerous way. The applications of nanotechnology play a vital role in many research fields. And therefore, this research, employs the implementation of nanotechnology approach such as silica-grapheme nanocomposite that could be able to minimize the Arsenic heavy metal contamination issues.